Structure and organization of the gene coding for the DNA binding protein of adenovirus type 5. - Kruijer, W (1981)
We have determined the nucleotide sequence of a region of adenovirus type 5 (Ad5) DNA located between map positions 61.7 and 71.4, which covers the gene form the 72 kD DNA binding protein (DBP) and the sequence encoding the amino-terminal part of the 100 kD protein. Sequence analysis of cDNA copies of DBP mRNA revealed the existence of two abundant species of spliced mRNA molecules. One species consists of two short leader sequences from positions 75.2 (67 and 68 nucleotides long) and 68.8 (77 nucleotides long), respectively, and the main body of the RNA molecules. The other species contains only the leader sequence from position 75.2 and the main body. The amino acid sequence of DBP is encoded entirely by a long open reading frame of 1587 nucleotides in the main body of DBP mRNA. From the nucleotide sequence of the DBP gene it can be derived that DBP contains 529 amino acid residues and has an actual molecular weight of 59,049 daltons. The sites of mutation in the mutants H5hr404 and H5ts125 were determined at the nucleotide level. Single nucleotide alterations were detected in H5hr404 and H5ts125 in the sequences corresponding to the amino-terminal part and the carboxy-terminal part of DBP, respectively. The implications of these mutations are discussed.